Effect of Two Physiological Regulators on Asexual Propagation of Cape Gooseberry (Physalis peruviana L.) under Greenhouse Conditions (2023)
The cape gooseberry is a plant of great nutritional and medicinal value. It is the most important exotic fruit exported by Colombia. It is normally sexually propagated, but its propagation by cuttings shortens its vegetative period by about one month. For asexual propagation, different plant growth regulators (PGRs) are usually used. Replacing synthetic PGRs with natural alternatives is becoming more common due to the high cost of synthetic PGRs and the risk of toxicity to plants, humans and animals from overuse. For this reason, the objective of the present study was to evaluate the effects of applying a synthetic and a natural rooting agent on the asexual propagation of Physalis peruviana L. For this, 11 cm long cuttings of adult plants of the Colombia ecotype were used and a completely randomized design (DCA) with three treatments (Aloe vera L., ANA 0.4% and control without hormone) and three replications was used. Once the cape gooseberry cuttings were established in the greenhouse, the survival percentage, rooting percentage, cutting height, and root length were evaluated. Survival and rooting percentage was 100% for all treatments due to the reserve levels of the plant material. The application of ANA 0.4% showed better results than the other treatments in root length. There were no significant differences in the height of the cuttings between the natural and synthetic rooting hormones. Furthermore, rooting was obtained for all the cuttings, even without the use of the hormone.